Exposure to ultrafine particles and respiratory hospitalisations in five European cities. Issue 3 (23rd June 2016) - Samoli, Evangelia; Andersen, Zorana Jovanovic; Katsouyanni, Klea; Hennig, Frauke; Kuhlbusch, Thomas A.J.; Bellander, Tom; Cattani, Giorgio; Cyrys, Josef; Forastiere, Francesco; Jacquemin, Bénédicte; Kulmala, Markku; Lanki, Timo; et al.
Epidemiological evidence on the associations between exposure to ultrafine particles (UFP), with aerodynamic electrical mobility diameters <100 nm, and health is limited. We gathered data on UFP from five European cities within 2001–2011 to investigate associations between short-term changes in concentrations and respiratory hospitalisations. We applied city-specific Poisson regression models and combined city-specific estimates to obtain pooled estimates. We evaluated the sensitivity of our findings to co-pollutant adjustment and investigated effect modification patterns by period of the year, age at admission and specific diagnoses. Our results for the whole time period do not support an association between UFP and respiratory hospitalisations, although we found suggestive associations among those 0–14 years old. We nevertheless report consistent adverse effect estimates during the warm period of the year, statistically significant after lag 2 when an increase by 10 000 particles per cm 3 was associated with a 4.27% (95% CI 1.68–6.92%) increase in hospitalisations. These effect estimates were robust to particles' mass or gaseous pollutants adjustment. Considering that our findings during the warm period may reflect better exposure assessment and that the main source of non-soluble UFP in urban areas is traffic, our results call for improved regulation of traffic emissions. Exposure to ultrafine particles may increase respiratory hospitalisations in the warm period irrespective of age group http://ow.ly/bGpo300znS1